Utilization of p-graph approach for pathway prediction of disinfection by-products of electrolyzed seawater for wastewater treatment - Almera, Maria Angela Roselle del Rosario (Animo Repository, 2023)
Using electrolyzed seawater as a disinfectant provides promising results for wastewater treatments since it produces hypochlorous acid, which has a strong disinfectant effect yet poses a threat to human health, along with chlorine and bromine, which are primary components in electrolyzed seawater that produces carcinogenic disinfection by-products, such as trihalomethanes. In this study, P-graph approach was utilized in identifying the number of pathways that will predict the least amount of potential DBPs using electrolyzed seawater as a disinfectant. Elementary reactions that take place during the disinfection process were first listed, then converted into P-graph models through P-graph Studio, and possible pathways for the formation of DBPs were highlighted. Using the Solution Structure Generation (SSG) algorithm, multiple structures were generated and filtered to identify the number of valid structures. Afterwards, the valid pathway which contained the most number of elementary reactions was translated into kinetic equations and was evaluated further. The kinetic equations obtained was evaluated using experimental data from the study of Nokes et al. (1999), which revealed that the equations from both are identical. With the challenges encountered regarding data availability, it is recommended for further studies to have a wider scope. Different software may also be considered, especially in the filtering and evaluating steps. Lastly, performance of an experiment with actual parameters is highly recommended to obtain better results